Microenvironment and autophagy cross-talk: Implications in cancer therapy. (May 2016) - Gomes, Luciana R.; Vessoni, Alexandre T.; Menck, Carlos F.M.
Graphical abstract: Abstract: There are many ongoing clinical trials to validate tumour microenvironment or autophagic pathway components as targets for anticancer therapies. Different components of the tumour microenvironment play important roles in tumour cell responses, directly affecting malignant transformation, drug resistance and metastasis. Autophagy is also related to chemotherapy responses by inducing tumour cell death or survival. Thus, the autophagy pathway may act as oncosuppressor, in addition to protecting cells from chemotherapy. The cross-talk between the microenvironment and autophagy is very complex and poorly understood. In a recent study using a three-dimensional (3D) cell culture model, the well-documented chemotherapy-mediated activation of autophagy was impaired in breast cancer cells, suggesting a context-dependent outcome for autophagy modulators, under the control of the p53 protein. A deeper understanding of this microenvironment/autophagy interplay may provide important clues for identifying differences in the tumour cell signalling network from in vitro basic research studies to the actual clinical context. In this work, we summarize the role of the microenvironment and autophagy in physiological and tumourigenic conditions, their interactions, and the challenges related to the use of drugs that target these pathways in cancer treatment protocols, emphasizing the potential use of 3D cell culture models in preclinical studies.